1980
DOI: 10.1111/j.1365-2125.1980.tb01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of mild analgesics.

Abstract: 1 Macro‐autoradiographic methods were used to assess the biodistribution of [3H]‐, or [14C]‐acidic (aspirin, indomethacin, phenylbutazone) and non‐acidic (antipyrine, aminopyrine, paracetamol) mild analgesics in rats with carrageenan‐induced inflammation. 2 At anti‐inflammatory doses all the acidic drugs (and/or their metabolites) were found to reach high concentrations in the stomach wall, liver, blood and bone marrow, kidney cortex and the inflamed tissue, that is, the tissues in which these drugs exert thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 11 publications
1
16
1
1
Order By: Relevance
“…The cellular in corporation of INDO may be involved in the anti-inflammatory action of INDO both in the PMN as a target cell, and in the inflamed areas due to the specific accumulation of this acidic drug. The last suggestion has already been demonstrated for acidic NSAIDs [8,9,10,29].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cellular in corporation of INDO may be involved in the anti-inflammatory action of INDO both in the PMN as a target cell, and in the inflamed areas due to the specific accumulation of this acidic drug. The last suggestion has already been demonstrated for acidic NSAIDs [8,9,10,29].…”
Section: Discussionmentioning
confidence: 97%
“…It has been established that INDO inhibits cycloox ygenase and various lipoxygenases [2,3], and that PMNs are an important source of arachidonate metabolites in acute inflammation [4]. Furthermore, many studies have demon strated that this drug can modulate the activ ity of PMNs in vivo and in vitro [5][6][7], INDO also accumulates in vivo in inflamed areas and acidic tissues [8][9][10]. Only few studies [11][12][13][14] have examined the association of non steroidal anti-inflammatory drugs (NSAIDs) with PMNs and none to date have examined the molecular interaction of INDO with PMNs.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that a consequential increase in mucosal permeability is transformed into a tissue reaction by mucosal exposure to luminal aggressive factors (7). The ion-trapping hypothesis (16), which postulates that accumulation of NSAID in gastric epithelial cells is dependent largely on interaction of the NSAID pKa and gastric luminal pH (locally), provides a possible explanation for drug absorption (along with molecular size, lipid solubility, dilution, and transit times), but not the mechanism of damage. The common action of acidic NSAIDs on mitochondrial metabolism, suggested previously by Whitehouse (17) and McDougall et a1 (18), provides a logical explanation of the mechanism of the "topical" phase of damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nonnarcotic analgesics without anti-inflammatory ac tivity, such as dipyrone and paracetamol, have not been associated with a risk of upper gastrointestinal bleeding in epidemiological studies [3,18], This good gastrointestinal tolerance is thought to be due not only to weak or absent inhibition of prostaglandin synthesis, but also to distinct pharmacokinetic properties [7][8][9], While acidic NSAIDs accumulate in the gastric mucosa, dipyrone and paraceta mol, which are weak bases, do not. A dose of 1 g t.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Nonacidic analgesics such as paracetamol, propyphenazone and dipyrone are poor inhibitors of pros taglandin synthesis and do not accumulate in the mucosa, which probably accounts for their greater tolerability [9], In addition, paracetamol has proved to be effective in lowering the analgesic dose of NSAID required, even in rheumatoid arthritis, for patients with gastrointestinal disturbances [10], Dipyrone has been shown to be an effective analgesic for a wide variety of indications, but very few data are available concerning its gastrointestinal toxicity. Despite the epidemiological evidence for the good gastrointestinal tolerability of dipyrone, direct ef fects of dipyrone (metamizole) on the gastrointestinal tract in humans have not yet been investigated in detail even if it has been shown that the ulcerogenic activity of dipyrone in rats is similar to that of paracetamol [11].…”
mentioning
confidence: 99%